THE CROSSWORD PUZZLE SUPPORT OF THE THINK PAIR SHARE COOPERATIVE LEARNING AND THE AFFECTNESS TO COGNITIVE ABILITY - Putri, Adhilla Prima; Zahra, Firda Az (Universe, 2024)
This research was motivated by the low student learning outcomes in science learning at 8th grade in Secondary School 34 Padang. It caused by the science learning process is still teacher-centered so that students are less active in the learning process. This study aims to find out how much influence of the cooperative model type think-pair-share assisted by crossword puzzles on students' cognitive abilities. The method used is a quasi-experimental method with a non-equivalent posttest only control group design. The population of this study was all students of 8th grade in Secondary School 34 Padang that consisted of 9 classes. The samples of this study were 32 students of class VIII-A and 30 students of class VIII-B. The sampling technique was done by purposive sampling technique. The results of the data analysis was carried out by using SPSS version 25 application which carried out by using a hypothesis test with independent sample t-test. The test results, a sig (2-tailed) value of 0.004 <0.05 which means is rejected and is accepted. It can be concluded that the cooperative model type think-pair-share assisted by crossword puzzles has an influence on students' cognitive abilities of students at Secondary School 34 Padang.